2014
DOI: 10.1007/s13204-014-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biosynthesized gold nanoparticles from aqueous extract of Chlorella vulgaris and their anti-pathogenic properties

Abstract: In this study, biosynthesis of self-assembled gold nanoparticles (GNPs) was accomplished using an aqueous extract of green microalga, Chlorella vulgaris. The optical, physical, chemical and bactericidal properties of the GNPs were investigated to identify their average shape and size, crystal nature, surface chemistry and toxicity, via UV-visible spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy and antimicrobial activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…4B) 16 . This results are in compliance with several reports indicating biogenic synthesis of nanoparticles such as palladium nanocrystals 16 , and gold 34 nanoparticles which indicated that diverse metabolites present in microalgae extracts such as polyphenols, sugars, terpenoids, proteins, phenolic acids, and enzymes are key responsible for reduction and stabilization of green nanoparticles 34,35 .
Figure 4FTIR spectrum of Chlorella aqueous extract ( A ), and biosynthesized ZnO NPs ( B ).
Figure 5Schematic illustration of the possible mechanism for the biogenic synthesis of ZnO NPs using aqueous Chlorella extract (algae-derived carbohydrate as bioreducing agent model).
…”
Section: Resultssupporting
confidence: 93%
“…4B) 16 . This results are in compliance with several reports indicating biogenic synthesis of nanoparticles such as palladium nanocrystals 16 , and gold 34 nanoparticles which indicated that diverse metabolites present in microalgae extracts such as polyphenols, sugars, terpenoids, proteins, phenolic acids, and enzymes are key responsible for reduction and stabilization of green nanoparticles 34,35 .
Figure 4FTIR spectrum of Chlorella aqueous extract ( A ), and biosynthesized ZnO NPs ( B ).
Figure 5Schematic illustration of the possible mechanism for the biogenic synthesis of ZnO NPs using aqueous Chlorella extract (algae-derived carbohydrate as bioreducing agent model).
…”
Section: Resultssupporting
confidence: 93%
“…However, the mechanism of biosynthesis of nanoparticles is still not well understood and requires more studies. e most plausible general mechanism is concluded that the functional groups existing in the plant extract such as alcohol, polyphenols, flavonoids, aromatic, and aliphatic amines play an important role in the green synthesis of ZnO NPs [80][81][82]. e aqueous extract of the plant that contains a high amount of organic components contributes to the metallic ion reduction processes.…”
Section: Mechanism Of Formation Of Biosynthesized Zno Npsmentioning
confidence: 99%
“…2 showed a distinct peak in the range of 3336, 2128, 1636, and 722 cm -1 representing the presence of capping molecules with the nanoparticles. The FTIR a major peak, was obtained at 1,636 cm -1 indicating the presence of amide-I and amide II bonding from capped peptides; Annamalai et al, reported similar results 35 . Fig.…”
Section: Fig 1: Synthesis Of Aunps Using C Pentandra Bark Extract mentioning
confidence: 75%